KIT and melanoma predisposition in pigs: sequence variants and association analysis. (15th March 2014) - Fernández‐Rodríguez, A.; Estellé, J.; Blin, A.; Muñoz, M.; Créchet, F.; Demenais, F.; Vincent‐Naulleau, S.; Bourneuf, E.
Summary KIT mutations have been detected in different cancer subtypes, including melanoma. The gene also has been extensively studied in farm animals for its prominent role in coat color. The present work aimed at detecting KIT variants in a porcine model of cutaneous melanoma, the melanoblastoma‐bearing Libechov Minipig (MeLiM). By sequencing exons and intron borders, 36 SNPs and one indel were identified. Of 10 coding SNPs, three were non‐synonymous mutations, likely to affect the protein conformation. A promising variant, located in exon 19 (p.Val870Ala), was genotyped in a MeLiM × Duroc cross, and an association analysis was conducted on several melanoma‐related traits. This variant showed a significant association with melanoma development, tumor ulceration and cutaneous invasion. In conclusion, although the KIT gene would not be a major causal gene for melanoma development in pig, its genetic variation could be influencing this trait.